120. Electron density calibration curve for Philips Brilliance Big Bore CT for radiotherapy: HU stability and comparison with Varian default curve. (December 2018) - Pinna, F.; Poggiu, A.; Bona, R.; Marini, P.
Abstract: Purpose: The calibration of the newly installed Philips Brilliance Big Bore CT scanner, finding the most appropriate curve (HU vs electron densities) for Varian Eclipse AAA algorithm. FOV dimensions, CT voltage, object dimensions and reconstruction filters are the major parameters that can affect the response curve, depending on the particular scanner model. They've been studied, and differences respect Varian default curve were evaluated. Methods and materials: The CIRS62M HEAD and BODY phantoms, equipped with low and high densities inserts, of known electron densities were used. Scans were made varying the position of inserts from the centre to the border of the test object, then varying separately CT voltage, FOV, test-object dimensions with respect to FOV, CT protocol (head vs body protocols), with particular attention to reconstruction filters. Test acquisitions regarded both allowed and not-allowed filters (Philips gives general indications about filters to be avoided for planning, cause their effect on HU is not negligible). Results: CT voltage and FOV dimensions have shown not to influence the response curve. Variability among allowed reconstruction filters is acceptable even for high HU (<2% at 1000 HU), while the not-allowed filters move the HU values till 3% and 12% (at 1000 HU, body and head respectively). With allowed filters, the factor mainly influencing the HU curve has proved to be the object dimension: the head phantom scanned with a body protocol, independently of FOV, (e.g head-and-neck or arm/leg scans) gives differences till 9% at 1000 HU: the head curve should be used. Conclusion: Measures analysis suggests to create two different curves for planning purposes, with the average data of allowed filters: (1) head and (2) body curves . Varian default curve is much similar to the head one, while differences are not negligible with the body curve extrapolating at very high densities: titanium HU is evaluated 5200 against Varian 5600.